1973
DOI: 10.1113/jphysiol.1973.sp010297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lateral cervical cord lesions on the respiratory rhythm of anaesthetized, decerebrate cats after vagotomy

Abstract: SUMMARY1. The lateral cervical cord of vagotomized, anaesthetized cats was superficially lesioned at the C3 or the C7 level before or after midcollicular decerebration.2. These cord lesions eliminated the inhibition of diaphragmatic discharge caused by chest compression. Previous work (Remmers, 1973) indicates that this change can be attributed to loss of reflex inhibition of inspiratory activity by intercostal afferents, probably as a result of interruption of tracts ascending in the lateral columns.3. Decere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The 1 mm deep cut, above or below the level of the phrenic outflow, had little influence on the spontaneous phrenic or recurrent laryngeal discharges in most cases. Similar observations were made by Remmers & Tsiaras (1973), who, in addition, found no significant change in end-tidal Pco2. Occasionally, a lesion at the C3 level, ipsilateral to the site of phrenic recording, diminished spontaneous phrenic discharge, and in one case all rhythmic discharge ceased.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The 1 mm deep cut, above or below the level of the phrenic outflow, had little influence on the spontaneous phrenic or recurrent laryngeal discharges in most cases. Similar observations were made by Remmers & Tsiaras (1973), who, in addition, found no significant change in end-tidal Pco2. Occasionally, a lesion at the C3 level, ipsilateral to the site of phrenic recording, diminished spontaneous phrenic discharge, and in one case all rhythmic discharge ceased.…”
Section: Resultssupporting
confidence: 89%
“…Effects I I in 1 a -AAid INTERCOSTAL REFLEXES 5 the sections were similar to those reported elsewhere (Remmers & Tsiaras, 1973). The 1 mm deep cut, above or below the level of the phrenic outflow, had little influence on the spontaneous phrenic or recurrent laryngeal discharges in most cases.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…White-matter sparing. In contusion animals, substantial white-matter damage was observed around the lesion epicenter, which would disrupt both descending ipsilateral-bulbospinal innervation (ventromedial and lateral columns) (Lipski et al 1994) and ascending propriospinal inputs (lateral columns) (Decima and von Euler 1969;Dimarco and Kowalski 2013;Remmers and Tsiaras 1973) to the phrenic nucleus. Of note, other studies, including those using higher contusion-injury forces, report similar patterns of white-matter injury encompassing the dorsal, lateral, and ventral funiculi (Awad et al 2013;Choi et al 2005;Lane et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[11] have recently shown the occurrence of muscle spindles and tonic activity in the human diaphragm, and such reflexes could operate in conditions involving a downward displacement of the diaphragm. Furthermore, several investigators have reported that chest compression in animals provoked alterations in phrenic efferent activity via intercostal-to-phrenic reflexes from both the middle and lower thoracic region [3,14]. The nar row scatter of the data points suggests, however, that the 4 subjects tested were able to adequately relax their respiratory muscles to obtain reliable PV curves of the chest wall in the strapped state as well (see below).…”
Section: Methodsmentioning
confidence: 84%